Interaction between Learning Styles (Sequential/Global) and the Density Level of Digital Game Motivational Elements (Binary/Ternary) and Its Impact on the Development of Digital Competitiveness among Educational Technology Students - AbouHashesh, Mohamed Radwan Ibrahim; Kahouf, Samir Ahmed Elsayed; Abdelrhman, Shaymaa Ahmed Ahmed Mohamed (Journal of Posthumanism, 2024)
The purpose of this study is to investigate the interaction between learning styles (sequential and global) and the density level of digital game motivational elements (binary and ternary) and their impact on the development of digital competitiveness among Educational Technology students. Relevant literature, theoretical frameworks, and market analyses were reviewed to establish the foundation of the study, which subsequently opened new avenues for future research. A 2×2 factorial experimental design was employed, wherein pre-test and post-test measures were used to assess the effect of the independent variables on digital competitiveness.The results indicate that sequential learning styles combined with a ternary level of digital game motivational elements yield higher digital competitiveness compared to other configurations. These findings provide critical insights into how tailored instructional strategies incorporating gamification can enhance digital competencies in educational settings. Data were collected from first-year Educational Technology students, and the outcomes have important implications for the design of digital learning environments and future academic research on gamification and digital engagement.